Complete Blood Count Alterations of COVID-19 Patients in Riyadh, Kingdom of Saudi Arabia. (31st January 2022) - Elderdery, Abozer Y.; Elkhalifa, Ahmed M. E.; Alsrhani, Abdullah; Zawbaee, Khalid I.; Alsurayea, Saad M.; Escandarani, Faisal K.; Alhamidi, Abdulaziz H.; Idris, Hadeil M. E.; Abbas, Anass M.; Shalabi, Manar G.; Mills, Jeremy
Abstract : This study is aimed at evaluating the association between Coronavirus disease 19 (COVID-19) and the primary complete blood count (CBC) parameters in confirmed positive patients. In a retrospective cross-sectional study, 384 files of patients with confirmed COVID-19 diagnosis hospitalized at King Saud Medical City, Riyadh, were chosen randomly as a study group for hematological parameters, with another 384 non-COVID-19 files of patients without history of any disease which could influence the hematological profile were selected as a control group. The gender, age, and nationality of the control group were matched with those of the study group. Anemia and thrombocytopenia prevalence was significantly higher in COVID-19 positive patients compared with negative. However, the positive cases were 3.4 times more likely to be anemic and approximately 5.3 times as likely to be thrombocytopenic, while the prevalence of leukopenia showed no statistical significance between the two groups. However, the Mean Cell Volume (MCV), Total White Blood Cell (WBC) count, lymphocyte count, and basophil count median values showed a nonsignificant difference between the two groups. Anemia and thrombocytopenia may be highly developed in severe positive cases, and therefore, further studies are recommended to validate these findings.